Scan without evidence of dopaminergic deficit: A 10-year retrospective study. (October 2016) - Nicastro, Nicolas; Garibotto, Valentina; Badoud, Simon; Burkhard, Pierre R.
Abstract: Introduction: 123 I-ioflupane SPECT is a powerful method to assess nigrostriatal dopamine system integrity. Several independent studies have shown that 1–15% of patients with suspected degenerative parkinsonism, mainly PD, have scans without evidence of dopaminergic deficit (SWEDD). It has been proposed that most SWEDD patients either present with a non-degenerative condition mimicking PD, such as atypical tremor or dystonia, or demonstrate an abnormal scan when repeated later. We here hypothesized that scan interpretation methods may also play a crucial yet underestimated role in this issue. Methods: We previously established age-dependent reference values of striatal uptake by analyzing scans from a cohort of patients with non-degenerative conditions. We then studied a large population with well-established degenerative parkinsonism (N = 410, 80% with PD), using identical imaging protocol, to evaluate the prevalence of patients with normal scans based on routine visual assessment. Each scan was eventually reassessed using the same automated method as for controls and a detailed 3D analysis. Results: Ten potential SWEDD cases (2.4%) were identified. However, both reassessment methods independently showed that these scans were all outside reference limits and/or visually abnormal when reexamined carefully, except for one case (0.2%) with corticobasal syndrome. Conclusion: SPECT misinterpretation emerges as an important contributor to the SWEDD population, suggesting that suspected SWEDD cases should prompt not only a serious diagnosis challenge but, equally important, a detailed scan reassessment. True SWEDD cases seem extremely rare in degenerative parkinsonism. We propose that the very concept of SWEDD is more confusing than helpful and should be definitely abandoned. Highlights: 1–15% patients with suspected Parkinson's disease have normal 123 I-Ioflupane SPECT. Non-degenerative conditions accounts for a large proportion of these results. We suggest scan misinterpretation may also play a role. We performed a visual and semi-quantitative assessment. Only one patient with corticobasal syndrome had a strictly normal SPECT.